An Insight into Textual Borrowing Practices of University-Level Students in Bosnia and Herzegovina - Jahic, Alma (Journal of Academic Writing, 2011)
Textual borrowing, a distinctive feature of academic writing, is a very complex practice which poses problems to novice English as a Second Language/English as a Foreign Language (ESL/EFL) writers. Students in Bosnia and Herzegovina (BiH) also encounter these problems when writing in English. The present study investigates the use of source texts in student essays in order to find out how BiH students incorporate borrowed text into their own. The first part of this paper provides a short theoretical background on the topic and offers insight into the BiH education system, while the second part of the paper presents the main research results which show a high incidence of inappropriate textual borrowing in student texts. It is argued that a stronger focus on teaching writing and more hours of explicit teaching are possible ways to overcome this problem.